Heyde syndrome revisited: anaemia and aortic stenosis. Issue 7 (July 2017) - Tjahjadi, Catherina; Wee, Yong; Hay, Karen; Tesar, Peter; Clarke, Andrew; Walters, Darren L.; Bett, Nicholas
Abstract: Background: The association of anaemia with aortic stenosis (AS) has been recognised for over 50 years; however, although there have been several sporadic reports, there are few data on the prevalence of this syndrome. Aims: We sought to compare the prevalence of anaemia in adults with AS with that of controls who had undergone coronary artery bypass grafting (CABG). Methods: We conducted a retrospective cohort study comparing pre‐procedural levels of haemoglobin in 1537 adults who underwent aortic valve replacement (AVR) for AS with 8025 contemporaneous patients who had CABG. We hypothesised that the prevalence of anaemia in patients with AS would be significantly higher than in the control group. Results: A total of 30.1% in the AVR group was anaemic compared to 16.2% in the CABG group. The mean haemoglobin concentration measured across the whole population was significantly lower (132 g/L) in AVR patients than in those who underwent CABG (138 g/L). In a multivariable model, haemoglobin levels varied significantly by treatment group, gender and age. The adjusted marginal mean haemoglobin value was 135.6 g/L in AVR patients compared to 137.3 g/L in CABG patients. Conclusions: The prevalence of anaemia was significantly greater in patients with AS than in a contemporaneous cohort that underwent CABG. This may indicate that Heyde syndrome is more common than has been generally appreciated and should be considered in the evaluation of anaemia in patients with AS.